Research on Gear Fault Diagnosis Method based on Local Characteristic Scale Decomposition and Mathematical Morphological Filtering - Jiaxing Qi; Weicheng Cui; Xiuping Zhao (Jixie chuandong)
In order to accurately diagnose gear faults, a gear fault diagnosis method based on local characteristic scale decomposition (LCD) and mathematical morphological filtering is proposed, which aims at the non-linear, non-stationary and low signal-to-noise ratio characteristics of vibration signals of early gear faults. Firstly, some Intrinsic Scale Components (ISCs) are obtained by local characteristic scale decomposition of gear vibration signals. Then, according to kurtosis criterion, the ISC with the largest kurtosis is selected as the fault characteristic component, and then filtered by morphological difference filter. Finally, the spectrum of the filtering results is obtained and the fault diagnosis is carried out. The feasibility and validity of the method are illustrated by analyzing the simulation results and experimental data. The results show that the method has the ability to suppress noise and extract fault shock characteristics, and can effectively realize the accurate diagnosis of gear fault.